KEMAMPUAN BERPIKIR KRITIS DAN LITERASI SAINS SISWA SMA DI JAKARTA TIMUR - Eka Putri Azrai; Ade - Suryanda; Ratna Dewi Wulaningsih; Umi Kulsum Sumiyati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
CRITICAL THINKING SKILLS AND SCIENTIFIC LITERACY OF HIGH SCHOOL STUDENTS IN EAST JAKARTA AbstractPISA in 2012 and 2015 shows the level of scientific literacy skills of Indonesian students is at a low level. One of the factors that influence the literacy ability of a person is the ability to think critically. The research aims to determine the relationship between critical thinking skills and high school students' scientific literacy in East Jakarta. The study was conducted in four state high schools in East Jakarta. A total of 167 students were taken as samples chosen by simple random sampling. The method used is descriptive with correlational studies. The average value of critical thinking skills is 45 in the category of lace. The level of scientific literacy of students is at level 3, which has been able to identify a scientific problem described clearly in the context of the level of science. The correlation coefficient obtained was 0.45, with a coefficient of determination of 0.199 and a simple regression model. Ŷ = 0.66 + 2.39X. This study concludes that there is a positive relationship between critical thinking skills and scientific literacy, where critical thinking skills contribute 19.9% to scientific literacy. AbstrakPISA tahun 2012 dan 2015 memperlihatkan kemampuan literasi sains anak Indonesia berada pada taraf rendah. Salah satu faktor yang mempengaruhi kemampuan literasi seorang adalah kemampuan berpikir kritis yang dimilikinya. Penelitian ini bertujuan mengetahui hubungan kemampuan berpikir kritis dengan literasi sains siswa SMA di Jakarta Timur. Penelitian dilaksanakan di empat SMA Negeri di Jakarta Timur. Sebanyak 167 siswa diambil sebagai sampel yang dipilih secara simple random sampling. Metode yang digunakan adalah deskriptif dengan studi korelasional. Rata-rata nilai kemampuan berpikir kritis sebesar 45 berkategori rendah. Level literasi sains siswa berada pada level 3, yaitu sudah mampu mengidentifikasi permasalahan ilmiah yang dideskripsikan dengan jelas pada tingkat konteks sains. Koefisien korelasi yang didapatkan sebesar 0,45 dengan koefisien determinasi sebesar 0,199 dan model regresi sederhana. Ŷ = 0,66 + 2,39X. Kesimpulan dari penelitian ini adalah terdapat hubungan antara kemampuan berpikir kritis dengan literasi sains, dimana kemampuan berpikir kritis memberikan kontribusi sebesar 19,9% terhadap literasi sains.